Change in Geographic Accessibility to Dental Clinics Affects Access to Care. (July 2023) - Yamamoto, T.; Hanazato, M.; Hikichi, H.; Kondo, K.; Osaka, K.; Kawachi, I.; Aida, J.
Access to dental clinics is a feature of the neighborhood service environment that may influence oral health care utilization. However, residential selection poses a challenge to causal inference. By studying the involuntary relocation of survivors of the 2011 Great East Japan Earthquake and Tsunami (GEJE), we examined the association between changes in geographic distance to dental clinics and dental visits. Longitudinal data from a cohort of older residents in Iwanuma City directly impacted by the GEJE were analyzed in this study. The baseline survey was conducted in 2010, 7 mo before the occurrence of GEJE, and a follow-up was conducted in 2016. Using Poisson regression models, we estimated the incidence rate ratios (IRR) and 95% confidence intervals (CIs) for the uptake of denture use (as a proxy for dental visits) according to changes in distance from the nearest dental clinic to their house. Age at baseline, housing damage by the disaster, deteriorating economic conditions, and worsened physical activity were used as confounders. Among the 1, 098 participants who had not worn dentures before the GEJE, 495 were men (45.1%), with a mean ± SD age at baseline of 74.0 ± 6.9 y. During the 6-year follow-up, 372 (33.9%) participants initiated denture use. Compared to those who experienced a large increase in distance to dental clinics (>370.0–6, 299.1 m), a large decrease in distance to dental clinics (>429.0–5, 382.6 m) was associated with a marginally significantly higher initiation of denture use among disaster survivors (IRR = 1.28; 95% CI, 0.99–1.66). The experience of major housing damage was independently associated with higher initiation of denture use (IRR = 1.77; 95% CI, 1.47−2.14). Improved geographic access to dental clinics may increase dental visits of disaster survivors. Further studies in non-disaster-affected areas are needed to generalize these findings.